Stress corrosion cracking of a high-strength friction-stir-welded joint of an Al–Zn–Mg–Zr alloy containing 0.25 wt.% Sc. (November 2015) - Deng, Ying; Peng, Bing; Xu, Guofu; Pan, Qinglin; Ye, Rui; Wang, Yingjun; Lu, Liying; Yin, Zhimin
Highlights: Investigate SCC behavior of a friction stir welded Al–Zn–Mg–Zr alloy with high Sc. Study microstructure and microchemistry in the friction stir welded joint. Establish the relationship between microstructure, microchemistry and SCC of joint. Reveal roles of anodic dissolution and hydrogen embrittlement mechanisms during SCC. Abstract: Stress corrosion cracking (SCC) behavior and mechanism of a friction stir welded Al–Zn–Mg–Zr alloy with 0.25 wt.% Sc were investigated. Impurity intermetallics and primary Al3 Sc x Zr1− x particles both crack perpendicular to tensile direction, whereas anodic dissolution only occurs around the former, initiating SCC. During cracking propagation, both anodic dissolution and hydrogen embrittlement operate. The thermo-mechanically affected zone on advancing side adjacent to weld nugget zone is most susceptible to SCC, which can be ascribed to the enrichment of impurity intermetallics, continuously distributed grain boundary precipitates and its stronger galvanic coupling with weld nugget zone from their greater microstructure and micro-chemistry differences.